The Use of Documents for Computer-Based Patient Records - Collen, M. F. (Methods of Information in Medicine, 1993)
Response to: Essin DJ. Intelligent processing of loosely structured documents as a strategy for organizing electronic health care records. Meth Inform Med 1993; 32: 265-8.